Enhancing hydrogen production through anode fed-batch mode and controlled cell voltage in a microbial electrolysis cell fully catalysed by microorganisms. (February 2022) - Lim, Swee Su; Fontmorin, Jean-Marie; Ikhmal Salehmin, Mohd Nur; Feng, Yujie; Scott, Keith; Yu, Eileen Hao
Abstract: A microbial electrolysis cell (MEC) fully catalysed by microorganisms is an attractive technology because it incorporates the state-of-the-art concept of converting organic waste to hydrogen with less external energy input than conventional electrolysers. In this work, the impact of the anode feed mode on the production of hydrogen by the biocathode was studied. In the first part, three feed modes and MEC performance in terms of hydrogen production were evaluated. The results showed the highest hydrogen production under the continuous mode (14.6 ± 0.4), followed by the fed-batch (12.7 ± 0.4) and batch (0 L m −2 cathode day −1 ) modes. On one hand, the continuous mode only increased by 15% even though the hydraulic retention time (HRT) (2.78 h) was lower than the fed-batch mode (HRT 5 h). A total replacement (fed-batch) rather than a constant mix of existing anolyte and fresh medium (continuous) was preferable. On the other hand, no hydrogen was produced in batch mode due to the extensive HRT (24 h) and bioanode starvation. In the second part, the fed-batch mode was further evaluated using a chronoamperometry method under a range of applied cell voltages of 0.3–1.6 V. Based on the potential evolution at the electrodes, three main regions were identified depending on the applied cell voltages: the cathode activation (<0.8 V), transition (0.8–1.1 V), and anode limitation (>1.1 V) regions. The maximum hydrogen production recorded was 12.1 ± 2.1 L m −2 cathode day −1  at 1.0 V applied voltage when the oxidation and reduction reactions at the anode and cathode were optimal (2.38 ± 0.61 A m −2 ). Microbial community analysis of the biocathode revealed that Alpha-, and Deltaproteobacteria were dominant in the samples with >70% abundance. At the genus level, Desulfovibrio sp. was the most abundant in the samples, showing that these microbes may be responsible for hydrogen evolution. Graphical abstract: Image 1 Highlights: Three cell voltage regions identified for MEC: cathode activation, transition and anode limitation. Fed-batch mode with HRT 5 h provided better control on bioanode activity and overall reaction kinetics. Maximum H2 production rate achieved as 12.1 ± 2.1 L m −2 day −1  at 1.0 V cell voltage in transition region.